Ability of a nurse specialist to diagnose simple headache disorders compared with consultant neurologists. Issue 8 (15th July 2005) - Clarke, C E; Edwards, J; Nicholl, D J; Sivaguru, A; Davies, P; Wiskin, C
Abstract : Objective: To compare the ability of a headache nurse specialist and consultant neurologists in diagnosing tension-type headache and migraine. Methods: An experienced neurology ward sister was trained in the differential diagnosis of headache disorders. Over six months, patients with non-acute headache disorders and role players trained to present with benign or sinister headaches were seen by both the nurse and a consultant neurologist. Both reached independent diagnoses of various headache disorders. Results: Consultants diagnosed 239 patients with tension-type headache (47%), migraine (39%), or other headache disorders (14%). The nurse agreed with the consultant in 92% of cases of tension-type headache, 91% of migraine, and 61% of other diagnoses. Where the nurse did not agree with the diagnosis, most would have been referred for a consultant opinion. Both the nurse and the doctors misdiagnosed the same three of 13 role players. The investigation rate of the consultants varied between 18% and 59%. Only one clinically relevant abnormality was found on head scans and this was strongly suspected clinically. Conclusions: A headache nurse specialist can be trained to diagnose tension-type headache and migraine. A nationwide nurse led diagnostic headache service could lead to substantial reduction in neurology waiting times.